Addressing the epidemiologic transition in the former Soviet Union: strategies for health system and public health reform in Russia. - Tulchinsky, T H (1996)
OBJECTIVES. This paper reviews Russia's health crisis, financing, and organization and public health reform needs. METHODS. The structure, policy, supply of services, and health status indicators of Russia's health system are examined. RESULTS. Longevity is declining; mortality rates from cardiovascular diseases and trauma are high and rising; maternal and infant mortality are high. Vaccine-preventable diseases have reappeared in epidemic form. Nutrition status is problematic. CONCLUSIONS. The crisis relates to Russia's economic transition, but it also goes deep into the former Soviet health system. The epidemiologic transition from a predominance of infectious to noninfectious diseases was addressed by increasing the quantity of services. The health system lacked mechanisms for epidemiologic or economic analysis and accountability to the public. Policy and funding favored hospitals over ambulatory care and individual routine checkups over community-oriented preventive approaches. Reform since 1991 has centered on national health insurance and decentralized management of services. A national health strategy to address fundamental public health problems is recommended.